(untitled) (Global Journal of Management and Business Research, 2016)
The purpose of this article is to review the recent trends related to corporate social responsibility (CSR) and financial reporting standards. The researcher presents four CSR background theories to evaluate the importance of sustainability in the financial reporting arena. The Big Four accounting firms are promoting the importance of adopting CSR in financial statements. Scholars and practitioners acknowledge that there is an existing relationship between corporate governance and CSR. The 7Ps presented in the study served as guidance for developing a sustainable and adequate CSR financial reporting system. The three pillars that support sustainability are environmental, social, and economic. It is expected that in the future the triple bottom line theory (TBL) will be known as integrated report (IR). Evidently, the adoption of corporate responsibility in financial statements has the ability to increase the amount of relevant information provided to shareholders and stock exchange markets around the world.